PESONA JEMBER DALAM FOTOGRAFI LANDSCAPE - Aditya Novianto Suwardi; I Made Saryana; Cokorda Istri Puspawati Nindhia (Retina Jurnal Fotografi, 2021)
Jember Regency is a regency located in the province of East Java, Indonesia. Jember Regency is rich in reliable tourism objects and has great opportunities to be developed in the future. There are various natural attractions that save many small paradises that are still not widely known to the public. The creation of this work aims to introduce tourist objects to the wider community in Jember Regency in Landscape photography works. In making this Landscape photography work, the creator has the opportunity to know more and introduce various tourism places in Jember Regency to the wider community. The emergence of the idea started from the creator who likes to take landscape photos where landscape photos are divided into various kinds and the creator was born in the city of Jember, so the creator wants to learn more about landscape photography and introduce tourist objects to the wider community in Jember Regency in the work of Landscape photography. The creator uses the method of exploration, observation and literature study in order to get maximum results. After doing these three methods, the creator took pictures of various tourist objects in the city of Jember. These tourist objects consist of Papuma Beach in Lojejer Village, Payangan Beach and Teluk Love in Sumberrejo Village, Tea Gambir Gardens in Sumberbaru Village, Damar Wulan Waterfall in Ledokombo Village, Sucopangepok Rice Fields. View of Sucopangepok Village and SJ88 in Sucopangepok Village, Tobacco House in Mumbulsari Village, Dan Rejo Dam in Tempurejo Village and still some tourist attractions in Jember. Keywords: Enchantment, Jember, Landscape Photography